Listen to the people : participant-observer evaluation of development projects - Salmen, Lawrence F (Oxford University Press New YorkUS, 1987)
Interprets the perception of reality of project beneficiaries of La Paz, Bolivia, and Guayaquil, Ecuador in the context of urban development projects and communicates that perception to host-country managers and Bank officials. Describes communities that served as project sites for the application of participant-observer evaluation. Discusses use of participant-observer evaluation in project areas and other countries where primary responsibility for the approach lay with host-country personnel. Elaborates the participant-observer evaluation method and summarizes its significance both as a project management tool and as a development activity.